#TITLE_ALTERNATIVE# - Fathrio (202 05 015), Ibnu
Abstract : Noise and outlier are inevitably encountered when CSAMT measurement are conducted. Stacking method is a usual measurement method to estimate impedance function .Stacking method is based on Least Square approximation where noise distribution is assumed gaussian. This method can be distorted easily by the presence of outliers and it cause misleading estimation. This thesis proposes a robust estimation of CSAMT impedance function which has a high resistance of outliers. Robust estimation is applied on CSAMT synthetic data which is contaminated by noise and outliers. Improvement of robust estimation result is also conducted using Hilbert transform and phase smoothing.